2022
DOI: 10.1001/jamaoto.2022.3360
|View full text |Cite
|
Sign up to set email alerts
|

American Thyroid Association Guidelines and National Trends in Management of Papillary Thyroid Carcinoma

Abstract: ImportanceOver time, the American Thyroid Association (ATA) guidelines have increasingly promoted more limited treatments for well-differentiated thyroid cancers.ObjectiveTo determine whether the 2009 and 2015 ATA guidelines were associated with changes in the management of low-risk papillary thyroid carcinomas on a national scale.Design, Setting, and ParticipantsThis historical cohort study used the National Cancer Database. All papillary thyroid carcinomas diagnosed from 2004 to 2019 in the National Cancer D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, approximately 80% of MRG-intermediate and MRG-low patients underwent total thyroidectomy in our study, of whom two-thirds received RAI ablation. This finding is consistent with a recent national study showing that 77% of low-risk thyroid cancers are treated with total thyroidectomy, as well as with other studies . Thus, an opportunity to deescalate surgery and decrease the burden of permanent surgical complications may be indicated for many patients with thyroid cancer when interpreted within the limitations of the lower power of our findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, approximately 80% of MRG-intermediate and MRG-low patients underwent total thyroidectomy in our study, of whom two-thirds received RAI ablation. This finding is consistent with a recent national study showing that 77% of low-risk thyroid cancers are treated with total thyroidectomy, as well as with other studies . Thus, an opportunity to deescalate surgery and decrease the burden of permanent surgical complications may be indicated for many patients with thyroid cancer when interpreted within the limitations of the lower power of our findings.…”
Section: Discussionsupporting
confidence: 93%
“…As observed in our study, the rate of thyroid lobectomy in patients with low‐risk differentiated thyroid cancer has increased over time and a growing number of patients did not receive radioactive iodine therapy after total or completion thyroidectomy. This indicates that changes in the 2015 ATA guidelines not only have implications for patients in America but also for patients in countries that have not formally adopted these guidelines such as The Netherlands 20 . While we cannot definitely determine the sole influence of the updated ATA guidelines, it is plausible that the network played a supportive role in enabling the implementation of these de‐escalated treatment approaches and ensuring consistent care throughout the region 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that changes in the 2015 ATA guidelines not only have implications for patients in America but also for patients in countries that have not formally adopted these guidelines such as The Netherlands. 20 While we cannot definitely determine the sole influence of the updated ATA guidelines, it is plausible that the network played a supportive role in enabling the implementation of these de-escalated treatment approaches and ensuring consistent care throughout the region. 21 Notably, de-escalating treatment strategies in the Southwestern of The Netherlands are often backed by the regional multidisciplinary tumor board, which benefits from the input of several experts in the field of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Studies from the Surveillance, Epidemiology, and End Results Program in the United States revealed increases in rates of treatment de-escalations in all aspects following the release of the 2015 ATA guidelines. [24] The risks of severe thyrotropin suppressive therapy would be more relevant in our present cohort because their age poses a greater risk for many age-related diseases. Moreover, recent data also showed that long-term TSH suppression in elderly patients with DTC was associated with sarcopenia and frailty.…”
Section: Discussionmentioning
confidence: 99%